2002
DOI: 10.1890/0012-9658(2002)083[1214:mbenzp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Masting by Eighteen New Zealand Plant Species: The Role of Temperature as a Synchronizing Cue

Abstract: Masting, the intermittent production of large flower or seed crops by a population of perennial plants, can enhance the reproductive success of participating plants and drive fluctuations in seed‐consumer populations and other ecosystem components over large geographic areas. The spatial and taxonomic extent over which masting is synchronized can determine its success in enhancing individual plant fitness as well as its ecosystem‐level effects, and it can indicate the types of proximal cues that enable reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
257
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 276 publications
(272 citation statements)
references
References 62 publications
11
257
1
3
Order By: Relevance
“…We used monitoring data from 1986 to 1999 at the study sites to calculate a multiple regression of A. scaphoides Xowering versus monthly, seasonal and annual precipitation. March precipitation was the best predictor of Xowering eVort (Table 1), consistent with the general pattern that weather conditions during bud initiation determine plant reproduction (Schauber et al 2002). March precipitation falls as a mixture of rain and snow in our study area.…”
Section: Supplemental Watering Experimentssupporting
confidence: 85%
See 1 more Smart Citation
“…We used monitoring data from 1986 to 1999 at the study sites to calculate a multiple regression of A. scaphoides Xowering versus monthly, seasonal and annual precipitation. March precipitation was the best predictor of Xowering eVort (Table 1), consistent with the general pattern that weather conditions during bud initiation determine plant reproduction (Schauber et al 2002). March precipitation falls as a mixture of rain and snow in our study area.…”
Section: Supplemental Watering Experimentssupporting
confidence: 85%
“…Weather conditions, particularly during bud initiation and development, determine Xowering eVort across a wide range of plant species, and appear to act as a synchronizing cue for mast seeding (e.g., Schauber et al 2002 and references cited therein), although weather cues for some species remain elusive (e.g., Crawley and Long 1995;Kobro et al 2003;Hamann 2004). Kelly and Sork (2002) review many examples of the Wtness advantages of synchronous seed production, including reduced seed predation in mast years and increased pollination eYciency in high-Xowering years (see also Forsyth 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Weather conditions have been suggested to synchronize the masting behaviour of plant populations, even involving different plant species over large geographic areas (Dahl and Strandhede 1996;Kelly 1994). Schauber et al (2002) showed that the mast seeding of 17 species of ecologically varied New Zealand plant species is highly synchronized, and that this synchrony is related to summer temperatures during critical periods of floral bud formation and differentiation. They suggest that this could be due to hormonal regulation affecting floral initiation.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been reported across a broad range of long-lived plants including grass and tree species (e.g., Chionochloa spp., Phormium spp., Picea spp., Quercus spp.) and in all types of forest ecosystems (Herrera et al 1998;Kelly et al 2000;Koenig and Knops 2000;Schauber et al 2002;Suzuki et al 2005;Lazaro et al 2006;Mduma et al 2007). Many studies have shown that masting is caused by an interaction between abiotic and biotic factors (Mduma et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, low productivity per se appears to favor higher variability in masting species (Kelly and Sork 2002). Environmental conditions such as temperature, rainfall and/or altitude, are likely to be involved as synchronizing cues at the local scale (Schauber et al 2002;Mduma et al 2007;Lamontagne and Boutin 2007). Furthermore, climate could act both as a proximate and ultimate explanation of masting, i.e., flowering only in response to a particular sequence of climate signals could be tied to fitness and thus selected.…”
Section: Introductionmentioning
confidence: 99%